PENINGKATAN KAPASITAS MANAJERIAL UMKM MELALUI PENYULUHAN DI DESA KEBON CAU, PAMARAYAN, BANTEN - Ende, Ende; Satria, Ezcky; Nugroho, Fico Adi (MAJU : Indonesian Journal of Community Empowerment, 2025)
The community service activity in Kebon Cau Village, Pamarayan District, Banten, aims to improve the managerial capacity of 20 Micro, Small, and Medium Enterprises (MSMEs). This activity was carried out because many MSMEs face obstacles in financial recording, business planning, and marketing strategies. The methods used include direct mentoring, practice-based training, and digital mentoring for financial record-keeping and product marketing. The results of the activity showed an increase in the managerial skills of the participants, including neat financial record-keeping skills, more effective marketing strategy planning, and the use of digital technology to support their businesses. The impact of this activity not only increased the independence and competitiveness of the businesses, but also fostered a collective awareness of the importance of structured business management, thus laying the foundation for sustainable local economic development.